“Hide Me” , Secure Application in Android Platform - Ya Abdullah, Norhaiza bt (Journal of Computing Technologies and Creative Content, 2019)
Currently in this era, applications for mobile platforms are being developed at a tremendous rate, but often without proper security implementation. Therefore, can cause serious information security and data privacy issues and can have severe impacts on users and organizations.This paper present “Hide Me” Android Application is focusing on Android user that want to safely secure the most user sensitive files. This application is suit for anyone who carries sensitive information with them while travelling, uploads sensitive files to servers on the Internet or wishes to protect sensitive information from being stolen. Those hide/lock process being encrypt by AES-256 encryption algorithms and also add-on another layer or security on database by hashed the message and key image using base 64 and MD5. Having encryption algorithms to secure the file is more secure ways by applying security concept which maintaining file confidentiality, integrity and availability.The result finding from the module testing and user acceptance testing approach was the positive feedback from respondent and actual result happen likely in expected result. In this approach, AES-256 encryption algorithms is help Android user to keep the file safe without worried if anything happen to their smartphone such as missing or phone theft..